The Analysis of Food Consumption and Nutritional Status of Pregnant Women Towards Preeclampsia in Dr. M. Ashari Hospital Pemalang 2018 - Nugroho, Nunung; Rustiana, Eunike Raffy (Public Health Perspective Journal, 2019)
Preeklampsia merupakan penyebab kematian ibu yang tinggi di Indonesia.Ã‚Â Preeclampsia is one of the causes of the high maternal mortality in Indonesia. More than 25% of maternal deaths in Indonesia are caused by preeclampsia. Preeclampsia can occur in women who lack and excess weight. One of Nurtitional Diagnosis is refers to the measurement of nutritional status of food consumption.This study aimed to analyze the food consumption and nutritional status of pregnant mothers towards preeclampsia in Dr. M. Ashari Hospital Pemalang 2018.This study is a quantitative research. Design of analytic observational study with retrospective case control approach. Research conducted from May to July 2018. The population of the entire postpartum mothers who give birth at Dr. M. Ashari Hospital in 2017 and a sample number of 128 obtained by the formula Lameshow. The instrument used was a 24-hour recall diet survey by AKG and questionnaires. Data analysis using Chi Square test.The results showed significant relationship between food consumption and nutritional status on the incidence of preeclampsia in Hospital Dr. M. Ashari Pemalang. Nutritional status has a greater impact with OR 1.523 against preeclampsia compared with the consumption of food. Pregnant women are expected to regulate weight gain and the amount of food consumption during pregnancy to prevent preeclampsia.